Evidence of convective transport in tropical West Pacific region during SHIVA experiment - Krysztofiak, Gisèle; Pfeilsticker, Klaus (Atmospheric science letters, 2018)
Air masses in the convective outflows of four large convective systems near Borneo Island in Malaysia were sampled in the height range 11-13 km within the frame of the SHIVA (Stratospheric Ozone: Halogen Impacts in a Varying Atmosphere) FP7 European project in November and December 2011. Correlated enhancements of CO, CH4 and the short-lived halogen species (CH3I and CHBr3) were detected when the aircraft crossed the anvils of the four systems. These enhancements were interpreted as the fingerprint of vertical transport from the boundary layer by the convective updraft and then horizontal advection in the outflow. For the four observations, the fraction f of air from the boundary layer ranged between 15 and 67%, showing the variability in transport efficiency depending on the dynamics of the convective system.
Gesehen am 16.02.2018